Phenotypic variability and disparities in treatment and outcomes of childhood arthritis throughout the world: an observational cohort study - Consolaro, Alessandro; Giancane, Gabriella; Alongi, Alessandra; van Dijkhuizen, Evert Hendrik Pieter; Aggarwal, Amita; Al-Mayouf, Sulaiman M.; Bovis, Francesca; De Inocencio, Jaime; Demirkaya, Erkan; Flato, Berit; Foell, Dirk; Garay, Stella Maris; et al. (Elsevier B.V., 2019)
Background To our knowledge, the characteristics and burden of childhood arthritis have never been studied on a worldwide basis. We aimed to investigate, with a cross-sectional study, the prevalence of disease categories, treatment methods, and disease status in patients from across different geographical areas and from countries with diverse wealth status. Methods In this multinational, cross-sectional, observational cohort study, we asked international paediatric rheumatologists from specialised centres to enrol children with a diagnosis of juvenile idiopathic arthritis, according to International League of Associations for Rheumatology criteria, who were seen consecutively for a period of 6 months. Each patient underwent retrospective and cross-sectional assessments, including measures of disease activity and damage and questionnaires on the wellbeing and quality of life of the children. We qualitatively compared the collected data across eight geographical areas, and we explored an association between disease activity and damage and a country's gross domestic product (GDP) with a multiple logistic regression analysis. Findings Between April 4, 2011, and Nov 21, 2016, 9081 patients were enrolled at 130 centres in 49 countries, grouped into eight geographical areas. Systemic arthritis (125 [33.0%] of 379 patients) and enthesitis-related arthritis (113 [29.8%] of 379) were more common in southeast Asia, whereas oligoarthritis was more prevalent in southern Europe (1360 [56.7%] of 2400) and rheumatoid factor-negative polyarthritis was more frequent in North America (165 [31.5%] of 523) than in the other areas. Prevalence of uveitis was highest in northern Europe (161 [19.1%] of 845 patients) and southern Europe (450 [18.8%] of 2400) and lowest in Latin America (54 [6.4%] of 849), Africa and Middle East (71 [5.9%] of 1209), and southeast Asia (19 [5.0%] of 379). Median age at disease onset was lower in southern Europe (3.5 years, IQR 1.9-7.3) than in other regions. Biological, disease-modifying antirheumatic drugs were prescribed more frequently in northern Europe and North America than in other geographical settings. Patients living in countries with lower GDP had greater disease activity and damage than those living in wealthier countries. Damage was associated with referral delay. Interpretation Our study documents a variability in prevalence of disease phenotypes and disparities in therapeutic choices and outcomes across geographical areas and wealth status of countries. The greater disease burden in lowerresource settings highlights the need for public health efforts aimed at improving equity in access to effective treatments and care for juvenile idiopathic arthritis. Copyright (C) 2019 Elsevier Ltd. All rights reserved.